Pembelajaran Bahasa Arab di UIN Maulana Malik Ibrahim dan STIBA Ar-Raayah - Ainun Suci Qurani; Septia Solihati; Nurul Al Fudiah; Siti Mufarokah; Istiadah Istiadah; Rizal Firdaus (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
Learning Arabic that is designed effectively will produce graduates who are competent in their fields. And a good Arabic learning design is identical to the use of materials, methods, strategies, media, and approaches that are appropriate to the situation and conditions, as well as the learning objectives to be achieved. This study aims to analyze the differences in the Arabic language learning curriculum at STIBA Ar-Rayah and UIN Maulana Malik Ibrahim. This study uses a qualitative approach, using a descriptive approach. As well as the technique of data collection is done by observation, interviews and utilizing documents that have to do with the title of the study. Assnd based on the results of research and comparative analysis of Arabic learning at STIBA Ar-Raayah and UIN Maulana Malik Ibrahim which are seen from the objectives, processes, methods, aspects of learning, media, as well as the evaluation of Arabic learning, there are differences and similarities in the learning curriculum used. of both.